2018
DOI: 10.1016/s0140-6736(18)30670-6
|View full text |Cite
|
Sign up to set email alerts
|

Child mortality in England compared with Sweden: a birth cohort study

Abstract: SummaryBackgroundChild mortality is almost twice as high in England compared with Sweden. We aimed to establish the extent to which adverse birth characteristics and socioeconomic factors explain this difference.MethodsWe developed nationally representative cohorts of singleton livebirths between Jan 1, 2003, and Dec 31, 2012, using the Hospital Episode Statistics in England, and the Swedish Medical Birth Register in Sweden, with longitudinal follow-up from linked hospital admissions and mortality records. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 40 publications
1
90
0
1
Order By: Relevance
“…This pattern was, however, less pronounced for infants associated with SBS/AHT criteria, who, surprisingly, had parents who scored better for education, living together, and smoking. Biological risk factors such as smoking, SGA, obesity, and prematurity are known to be more prevalent among socioeconomically disadvantaged individuals, and socioeconomic factors are also associated with child morbidity and child mortality . SGA and prematurity are associated with SDH, and in addition to these, obesity is associated with infant metabolic bone disease .…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was, however, less pronounced for infants associated with SBS/AHT criteria, who, surprisingly, had parents who scored better for education, living together, and smoking. Biological risk factors such as smoking, SGA, obesity, and prematurity are known to be more prevalent among socioeconomically disadvantaged individuals, and socioeconomic factors are also associated with child morbidity and child mortality . SGA and prematurity are associated with SDH, and in addition to these, obesity is associated with infant metabolic bone disease .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors identified by Zylbersztejn et al 1 were that smoking during pregnancy was much less common in Sweden than in England (6.5% vs 12%, 2010), although there are some worries that the popular use of oral tobacco, or snus, in Sweden may have similar negative effects. Obesity is also more common among pregnant women in England.…”
mentioning
confidence: 96%
“…Zylbersztejn et al 1 also reported that deaths due to congenital malformations were more common in England than Sweden (43 vs 29/100 000 singleton live births). This could partially be due to the higher smoking and obesity rates in England.…”
mentioning
confidence: 97%
See 2 more Smart Citations